2006
DOI: 10.1080/14034940510032194
|View full text |Cite
|
Sign up to set email alerts
|

Macro-organizational factors, the incidence of work disability, and work ability among the total workforce of home care workers in Sweden

Abstract: The differences in the municipal proportion of work ability incidence indicate a preventive potential, especially related to employment and return to work after sick leave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 26 publications
1
29
0
1
Order By: Relevance
“…Explanations to these differences were, in the first step, investigated through epidemiological register-based studies. However, macro-socioeconomic and sociodemographic factors explained only 12Á19% of the variation of occupational disorders (Dellve et al, 2003b) and 33Á34% of long-term sick leave or disability pension (Dellve et al, 2006). Age structures of HCWs and the unemployment level were related to the incidence rate, in this study and in other studies (Brooker, Frank & Tarasuk, 1997;Shannon, Mayr & Haines, 1997).…”
Section: Occupational Disorders Among Home Care Workerssupporting
confidence: 47%
See 2 more Smart Citations
“…Explanations to these differences were, in the first step, investigated through epidemiological register-based studies. However, macro-socioeconomic and sociodemographic factors explained only 12Á19% of the variation of occupational disorders (Dellve et al, 2003b) and 33Á34% of long-term sick leave or disability pension (Dellve et al, 2006). Age structures of HCWs and the unemployment level were related to the incidence rate, in this study and in other studies (Brooker, Frank & Tarasuk, 1997;Shannon, Mayr & Haines, 1997).…”
Section: Occupational Disorders Among Home Care Workerssupporting
confidence: 47%
“…Earlier studies showed great variations in organizational incidence of occupational disorders, as well as for long-term sick leave and disability pension among HCW in Sweden (Dellve, Allebeck et al, 2003;Dellve, Karlberg, Allebeck, Herloff & Hagberg, 2006). Nevertheless, factors that usually confound comparisons, like rights and obligations related to employment and workers' compensation, are nationally regulated.…”
Section: Occupational Disorders Among Home Care Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a high prevalence of employees on long-term sick leave in Sweden (2), with the highest prevalence seen among women working in human service organizations (HSO) (3)(4)(5)(6). HSO employees encompass, for example, workers in schools, preschools, home care service, and nursing or disabled-care homes who are in direct contact with clients or responsible for cleaning, cooking, or administration.…”
mentioning
confidence: 99%
“…The importance of macro organizational factors on Long Term Disability (LTD) (sick leave program for absences typically over 26 weeks) incidence was demonstrated with municipal employees in Sweden, finding that workplace factors were related to work disability (Dellve et al, 2006).…”
Section: Antecedents To Sick Leave / Work Disabilitymentioning
confidence: 99%